Effect of i.v. immunoglobulin in the first 4 days of illness in Kawasaki disease. Issue 4 (26th February 2018) - Shiozawa, Yusuke; Inuzuka, Ryo; Shindo, Takahiro; Mafune, Ryo; Hayashi, Taiyu; Hirata, Yoichiro; Shimizu, Nobutaka; Inatomi, Jun; Yokoyama, Yoshiki; Namai, Yoshiyuki; Oda, Yoichiro; Takamizawa, Masaru; et al.
Abstract: Background: Although early treatment of Kawasaki disease (KD) with i.v. immunoglobulin (IVIG) is expected to prevent coronary artery abnormalities, the effectiveness of IVIG by day 4 of illness remains to be determined. Methods: This was a multi‐institutional, retrospective cohort study. Patients diagnosed with KD at ≤4 days of illness were divided into two groups: those who received initial IVIG before and on day 5 of illness. Baseline characteristics were adjusted using propensity scores. The primary endpoint was the need for additional treatment. Results: Of 339 patients diagnosed with KD by day 4, 181 and 158 received IVIG before and on day 5 of illness, respectively. Patients in the early treatment group had more adverse prognostic factors: infancy, early onset of the principal symptoms, and abnormal laboratory data. We thus adjusted baseline characteristics before treatment decisions using propensity scores. Propensity score matching of the two groups yielded 100 observations. More patients required additional treatment in the matched early treatment group: 37% vs 24% (adjusted OR, 1.7; 95%CI: 1.06–2.8; P = 0.047). The difference was more pronounced for risk of relapse after initial resolution of fever: 14% vs 5.0% (adjusted OR, 3.2; 95%CI: 1.3–7.7; P = 0.02). The risk of coronary artery lesion did not differ significantly. Conclusions: IVIG treatment by day 4 of illness is associated with the requirement for additional treatment even after adjustment of baseline characteristics. Increased resistance to IVIG when given by day 4 should be considered in order to improve the treatment regimen for early‐diagnosed KD.